Universal access to sanitary products: A South African case study - Mokobi, Zamaswazi Vuyiswa (University of the Witwatersrand, Johannesburg, 2021)
Menstruation, which occurs as a result of the basic biology of a female who is of reproductive age is sadly a burden to many who experience it. Many women and young girls struggle with accessing basic facilities required to adequately manage their menstruation in a healthy manner. The ability to manage menstruation in a healthy manner is now internationally recognised as an essential human right that is a requirement for the realisation of gender equality. Not having access to sanitary products impedes women and girls’ human right to manage their menstruation. The South African government has intervened to make sanitary products more affordable and available to the female population through the implementation of the Sanitary Dignity Framework and the zero VAT rating of disposable sanitary pads. Through the Framework, government affirms “its commitment to the provision of sanitary dignity to indigent persons [and] that it will fund the provision of sanitary products” (Department: Women, Youth and Persons with Disabilities, 2019). The Framework aims “to promote sanitary dignity and to provide norms and standards [for the provision] of sanitary products to indigent persons” (Ibid). These interventions are aimed at achieving universal access to sanitary products. Achieving universal access is premised on ensuring that a service or product is acceptable, affordable and available to all. This research explores the effects of these government interventions on the achievement of universal access to sanitary products in South Africa. It is based on document analysis, literature review and the use of video recordings. Government’s interventions indicate that there is a political will to intervene in the plight to achieve universal access to sanitary products however these interventions have been minimally impactful. A finding of this research is that the zero rating of sanitary pads has had a questionable impact on the lives of poor females and seems to have been a decision unsupported by evidence of its impact. The Framework prioritizes the sanitary needs of some poor females who meet the definition of indigent persons over the sanitary needs of those who do not. An indigent person is defined as a “woman [or girl] who, due to poverty, lacks necessities of life such as sanitary products and other requirements to achieve sanitary dignity” (Ibid) and who falls within defined categories of women and girls that are considered to be indigent under the Framework. These categories include girls who attend quintiles 1 – 3 schools, girls who live in child-headed homes, and females who are admitted to state-owned institutions. The narrow definition of the Framework’s beneficiaries curtails the reach of the sanitary dignity programme (SDP) in terms of which free sanitary products are supplied to indigent persons, and excludes many poor females from having their sanitary product needs met. In addition, to date, the implementation of the SDP has been characterised by financial constraints, lack of uniformity and a general disorganisation. These government interventions have had a limited impact in achieving universal access to sanitary products in South Africa
A research article submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfillment of the requirements for the degree of Master of Business Administration Johannesburg, 2021
Keywords: Universal access; Sanitary dignity; Menstrual health/hygiene management; MHM; Sanitary Dignity Framework; Government intervention; UCTD; SDG-8: Decent work and economic growth